2012
DOI: 10.1073/pnas.1209954109
|View full text |Cite
|
Sign up to set email alerts
|

Insights into salt tolerance from the genome of Thellungiella salsuginea

Abstract: Thellungiella salsuginea, a close relative of Arabidopsis , represents an extremophile model for abiotic stress tolerance studies. We present the draft sequence of the T. salsuginea genome, assembled based on ∼134-fold coverage to seven chromosomes with a coding capacity of at least 28,457 genes. This genome provides resources and evidence about the nature of defense mechanisms constituting the genetic basis underlying plant abiotic stress tolerance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
249
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(259 citation statements)
references
References 43 publications
8
249
0
1
Order By: Relevance
“…2 and Supplementary Tables S23-S26). In this regard, the Na þ /K þ transporter HKT1 is of particular interest, because it is similarly expanded as tandem duplicated copies in both T. parvula 16 and T. salsuginea 43 . Further functional analysis of this gene family is needed to understand its critical role in salt tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and Supplementary Tables S23-S26). In this regard, the Na þ /K þ transporter HKT1 is of particular interest, because it is similarly expanded as tandem duplicated copies in both T. parvula 16 and T. salsuginea 43 . Further functional analysis of this gene family is needed to understand its critical role in salt tolerance in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted on the genetic and molecular mechanisms underlying salt tolerance in plants 18,19,30,31 , and have included genomic analyses of the extremophiles Thellungiella parvula 16 and T. salsuginea 43 . However, our current understanding of these aspects of salt tolerance remains limited, especially for woody plants 22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the caveats noted above concerning stress durations and intensities, this result suggests that adaptation to combined salt and heat stresses is more difficult than adaptation to the other combined stresses assessed here. Nonetheless, such a conclusion may only apply to temperate plants with similar ecologies to Arabidopsis, given the extent of adaptive diversity in related plants such as the halophyte Thellungiella salsuginea (Wu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thellungiella salsuginea, an extremophile closely related to Arabidopsis, has 28 Hsfs, supporting the importance of this transcription factor family in abiotic stress responses (55). A previous transcriptomic study revealed the involvement of HsfB2b in the necrotrophic pathogen response, but the direct molecular target of HsfB2b is in the corresponding signaling pathway(s) remains unclear (26).…”
Section: Discussionmentioning
confidence: 99%